IL-10 G-1082A gene polymorphism and susceptibility to upper respiratory tract infection among endurance athletes - Zehsaz, F.; Farhangi, N.; Monfaredan, A.; Tabatabaei Seyed, M. (The Journal of Sports Medicine and Physical Fitness, 2015)
AIM: The aim of this study was to investigate the influence of IL-10 gene polymorphisms on URTI incidence.